Electronic and superconducting properties of hydrogenated graphene from first-principles calculations - Lu, Qing; Ding, Chi; Wang, Xiaomeng; Chen, Tong; Sun, Jian (New journal of physics, 2022)
We performed first-principles calculations on two hydrogenated graphene systems with different hydrogen coverages, C 8 H 2 and C 50 H 2 , to analyze their electronic and superconducting properties. Our results show that their electronic properties are highly correlated to the hydrogenation positions. If the two hydrogen atoms are attached to the same sublattice, the final system will be ferromagnetic. Otherwise, it will maintain nonmagnetic rather than anti-ferromagnetic. Moreover, the distance between the doped hydrogens can trigger the movement of Dirac points, and even annihilate Dirac points when the distance is close to the maximum. We further studied their superconducting properties by applying hole doping and tensile strains. The results show that the superconducting transition temperature T c increases with more holes and reaches its maximum of about 20.2 K at the critical doping level ( x c = 0.17 holes/cell). Our results show that the superconductivity mainly originates from the coupling between the out-of-plane lattice vibration modes and the electronic p z orbitals of carbon atoms. The increase of T c can be attributed to the stronger coupling between the electrons and the low-frequency phonon. However, the application of biaxial and uniaxial tensile strain will depress the superconductivity because of the modulation of the low-frequency phonon. It is worthy to note that weak anharmonicity exists in the hydrogenated graphene systems. This work provides a systematic study on tuning the superconductivity of hydrogenated graphene.